PENGARUH APLIKASI E-LEARNING TERHADAP MINAT DANHASIL BELAJAR SISWA - Jama’atin Nuryah; Mahmud; Fauziah Rusmala Dewi (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2022)
This study aims to determine 1) the effect of the application of E-Learningon interest in learning theme 4 material Natural Resources for fourth gradestudents of Madarsah Ibtidaiyah Negeri 3 Mojokerto, 2) the effect of ELearning application on learning outcomes of theme 4 material on NaturalResources for fourth grade students of Madarsah Ibtidaiyah Negeri 3Mojokerto. Associative quantitative research. The population in this studywere 56 students in grade IV. Research instrument Using the method ofquestionnaires, tests, observations, and documentation. To carry out theresearch using simple linear regression. The results of the study (1) there isa significant effect between the E-Learning application variables on interestin learning with a value of tcount > ttable (16.145 > 1.671) and a significantvalue of 0.000 <0.05, which means that the E-Learning application variableaffects interest in learning by contributing of 82.8% the rest 17.2% (2) thereis an influence between the application of E-Learning on learning outcomeswith a value of tcount > ttable (4.103 > 1.671) and a significant value of0.000 <0.05 which means that the E-Learning application variable has aneffect on interest in learning with a contribution of 48.7% the remaining51.3%